The recursive formula
can be used to generate the shown sequence
Step-by-step explanation:
Recursive formula is the formula that is used to generate the next term of a sequence using previous term.
The general form of arithmetic sequence's recursive formula is:
![a_n = a_{n-1}+d](https://tex.z-dn.net/?f=a_n%20%3D%20a_%7Bn-1%7D%2Bd)
Given
5,-1,-7,-13,-19
Here
![a_1 = 5\\a_2 = -1\\a_3 = -7](https://tex.z-dn.net/?f=a_1%20%3D%205%5C%5Ca_2%20%3D%20-1%5C%5Ca_3%20%3D%20-7)
First of all we have to find the common difference of the sequence.
So,
![d = a_2 -a_1 = -1-5 = -6\\d = a_3-a_2 = -7+1 = -6](https://tex.z-dn.net/?f=d%20%3D%20a_2%20-a_1%20%3D%20-1-5%20%3D%20-6%5C%5Cd%20%3D%20a_3-a_2%20%3D%20-7%2B1%20%3D%20-6)
Putting the value of d in the general recursive formula
![a_n = a_{n-1}-6](https://tex.z-dn.net/?f=a_n%20%3D%20a_%7Bn-1%7D-6)
Hence,
The recursive formula
can be used to generate the shown sequence
Keywords: Sequence, arithmetic sequence
Learn more about arithmetic sequence at:
#LearnwithBrainly
The area of the arrow it's 660 cm.
Answer: 18
Step-by-step explanation:
this is because complementary angles add up to 90 degrees so you would just subtract 72 from 90 to get your answer :)
An exponential model can be described by the function
![f(x) = a(b)^x](https://tex.z-dn.net/?f=f%28x%29%20%3D%20a%28b%29%5Ex)
where: a is the initial population or the starting number, b is the base and x is the number of periods elapsed.
When the base of an exponential model is greater than 1 it is called a growth factor, but when it is less than 1 it is called a decay factor.
Given the exponential model
![n=20.5(0.6394)^t](https://tex.z-dn.net/?f=n%3D20.5%280.6394%29%5Et)
n is the final output of the exponential model, 20.5 is the starting number, 0.6394 is the base and t is the number of periods/time elapsed.
Here, the base is 0.6394 which is less than 1, hence a decay factor.
Therefore, <span>the
base, b, of the exponential model is 0.6394; It is a
decay factor.</span>
Answer:5.6 x 10^5
Step-by-step explanation:
When ever we hear sum, what comes to our mind must be addition
Here we are Adding 5.3 x 10 to the fifth power= 5.3 x 10^5 to
3.8 x 10 to the fourth power = 3.8 x 10^4
First,
Expanding the scientific notation we have that
5.3 x 10^5 = 530,000
3.8 x 10^4= 38,000
Add = 568,000
Putting back in Scientific notation we have 568000 = 5.6 x 10^5